Opera omnia - Cicero, Marcus Tullius 106-43 BC; Ernesti, Johann August 1707-1781 (Halle a.d. Saale Waisenhaus [Orphanotropheum], 1774)
Marcus Tullius Cicero (106 BC-43 BC) was a Roman statesman, lawyer, scholar, philosopher, writer and Academic skeptic, who tried to uphold optimate principles during the political crises that led to the establishment of the Roman Empire. His extensive writings include treatises on rhetoric, philosophy and politics. He is considered one of Rome's greatest orators and prose stylists and the innovator of what became known as "Ciceronian rhetoric".
Complete; contains vols. I, II/1, II,2 (Orationes), III/1, III/2 (Epistolæ ad Atticum, Q. Fratrem et Brutum), IV/1, IV/2 (Opera philosoph[ica] Fragmenta scriptorum deperitorum) and a Clavis.
Keywords: Classical Antiquity (8th Century BC-6th Century AD); 18th Century (1701-1800); Philosophy; Rhetoric; Politics; Rome (Italy)